1.
а)
144a²+24ab+b² = (12a)² + 2·12a·b+b² = (12a+b)²
б)
-9x⁴y⁸+12x²y⁴-4= -(9x⁴y⁸-12x²y⁴+4)= - (3x²y⁴-2)²
в)
![\frac{1}{16}p^{4}-p^{2}+4=(\frac{1}{4}p^2)^2-2*\frac{1}{4}p^2*2+2^2=(\frac{1}{4}p^2-2)^2 \frac{1}{16}p^{4}-p^{2}+4=(\frac{1}{4}p^2)^2-2*\frac{1}{4}p^2*2+2^2=(\frac{1}{4}p^2-2)^2](https://tex.z-dn.net/?f=%5Cfrac%7B1%7D%7B16%7Dp%5E%7B4%7D-p%5E%7B2%7D%2B4%3D%28%5Cfrac%7B1%7D%7B4%7Dp%5E2%29%5E2-2%2A%5Cfrac%7B1%7D%7B4%7Dp%5E2%2A2%2B2%5E2%3D%28%5Cfrac%7B1%7D%7B4%7Dp%5E2-2%29%5E2)
2.
a)
(2a-b²)² = 4a² - 2·2a·b² + b⁴ = 4a² - 4ab² + b⁴
Ответ: 4ab²
б)
(3c³ + П)² = 4d⁴ + 12c³d² + 9c⁶ = (3c³)² + 2·3c³·2d² + (2d²)² = (3c³ + 2d²)²
Ответ: 2d²